2012
DOI: 10.1016/j.cvfa.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Early Clinical Detection of Emerging Diseases in Food Animals and Zoonoses: Two Cases

Abstract: In case diseases of food-producing animals or zoonoses (re-)emerge, early clinical decision making is of major importance. In this particular condition, it is difficult to apply a classical evidence-based veterinary medicine process, because of a lack of available published data. A method based on the partition of field clinical observations (evidences) could be developed as an interesting alternative approach. The classification and regression tree (CART) analysis was used to improve the early clinical detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The reproductive indicators related to the Leptospira serovars found in this study, by X 2 test, demonstrated significant association between the average of SB and the serovar Pomona; these results are in accordance with the literature since this serovar has the swine species as reservoir, its related with the presence of the disease and has been found associated with the production of piglets born dead [41].…”
Section: Discussionsupporting
confidence: 92%
“…The reproductive indicators related to the Leptospira serovars found in this study, by X 2 test, demonstrated significant association between the average of SB and the serovar Pomona; these results are in accordance with the literature since this serovar has the swine species as reservoir, its related with the presence of the disease and has been found associated with the production of piglets born dead [41].…”
Section: Discussionsupporting
confidence: 92%
“…In the past, other powerful clinical decision support tools were developed and found that the combination of clinical signs with different frequencies (high and low) are valuable, especially for emerging diseases (e.g. [24,28,[38][39][40]). For the probability, the scale of colour is related to the increasing of its value (green to red).…”
Section: Plos Onementioning
confidence: 99%
“…Bats may have been the original hosts of many viruses because of their unusual host defense systems and immune tolerance, which allows viruses to coexist in bats without causing disease [Hauser et al, 2021;Irving et al, 2021;Parolin et al, 2021]. Additionally, bovine spongiform encephalopathy and endemic zoonotic diseases such as rabies are still prevalent in many countries [Saegerman et al, 2012].…”
Section: Viral Food Poisoningmentioning
confidence: 99%
“…According to a Loma Linda University study, vegetarians live 7 years longer and vegans 15 years longer than meat eaters. It is surprising that more humans have not come to realize this fact and still have not altered their lifestyles in this simple way to avoid so many of the natural causes of human suffering [Schierstaedt et al, 2019]. Several of these health-endangering agents, causing morbidity and mortality, will be described in sequence in this article.…”
Section: Introductionmentioning
confidence: 99%